Software quality model based on development team characteristics - Hamidreza Asfa; Taghi Javdani Gandomani (International Journal of Electrical and Computer Engineering (IJECE), 2023)
Many factors have a significant impact on producing high-quality software products. Development team members are among the most important factors. Paying attention to the quality from this perspective will be a good innovation in the software development industry. Given that team members play a very important role in software products, this study tries to focus specifically on team characteristics in software product quality and provide a qualitative model based on this. The required data were collected through observations and interviews with project managers and development team members in several companies under study. Then, data were analyzed through hierarchical analysis. According to the results, the use of this model led to the improvement of the software development process so that the team members were satisfied with it. Also, time management was improved, and the customer expressed his satisfaction with the use of this model. Finally, data analysis showed that this model may lead to faster product delivery.